Mahasiswa Mengabdi: Menguatkan Generasi Qur’ani, Melek Literasi, dan Mandiri Ekonomi - Belia Agustina; Soca Anggraini; Siti Zumrotus Sa’adah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Students as agents of change play an important role in the process of community development, not only in the academic environment but also in responding to various social issues. Community service is part of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education), which emphasizes the application of knowledge while improving the social, spiritual, and economic quality of society. This study explores the implementation of the “Student Service: Al-Qur'an Generation, Literacy, and Economic Independence” program in Merambung Village, Tangkit Hamlet. This program focuses on three main aspects, namely strengthening religious education through Al-Qur'an teaching at the Al-Qur'an Education Park (TPA), improving basic literacy through guidance in reading, writing, and arithmetic, and empowering the local economy through assistance for micro, small, and medium enterprises (MSMEs). The Participatory Action Research (PAR) method was used, actively involving the community in every stage of the program's implementation. The results of the study showed a significant increase in the ability to read the Qur'an and the application of spiritual values, an increase in interest and skills in basic literacy, and an increase in the competitiveness and independence of MSME actors through training and the use of promotional media. In addition to providing direct benefits to the community, this program also helped develop students' capacity in the application of knowledge, social empathy, and leadership competencies. The findings of this study confirm.